2001
DOI: 10.1164/ajrccm.163.1.2005009
|View full text |Cite
|
Sign up to set email alerts
|

Health Status Deterioration in Patients with Chronic Obstructive Pulmonary Disease

Abstract: An accelerated decline of FEV 1 is well-documented in patients with chronic obstructive pulmonary disease (COPD). Although FEV 1 is a useful measure for diagnosis and prognosis, it is neither a good predictor of the symptomatic response to treatment in COPD (1) nor of the likelihood of hospitalization (2). This has led to the use of generic and disease-specific questionnaires to measure the impact of COPD on health status. Crosssectional studies have shown that patient populations with a lower FEV 1 have worse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
198
4
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(242 citation statements)
references
References 17 publications
30
198
4
10
Order By: Relevance
“…In a study conducted in England and involving COPD patients, FEV 1 was found to correlate with the physical functioning, role-physical, social functioning, and general health domains, whose r values ranged from 0.15 to 0.25 (p < 0.001 for all). (25) In two other studies, FEV 1 was found to correlate with the SF-36 physical component summary (r = 0.38; p = 0.012), (10) as well as with a visual analog scale that rates health status (r = 0.19; p < 0.05). (26) Anemia, in addition to being a predictor of mortality in COPD patients on LTOT, can contribute to increasing dyspnea and cause exercise limitation.…”
Section: Discussionmentioning
confidence: 87%
“…In a study conducted in England and involving COPD patients, FEV 1 was found to correlate with the physical functioning, role-physical, social functioning, and general health domains, whose r values ranged from 0.15 to 0.25 (p < 0.001 for all). (25) In two other studies, FEV 1 was found to correlate with the SF-36 physical component summary (r = 0.38; p = 0.012), (10) as well as with a visual analog scale that rates health status (r = 0.19; p < 0.05). (26) Anemia, in addition to being a predictor of mortality in COPD patients on LTOT, can contribute to increasing dyspnea and cause exercise limitation.…”
Section: Discussionmentioning
confidence: 87%
“…The COPD patients in this study were in advanced stages of their illnesses and therefore, the possibilities for improvement with respect to physical aspects of QoL were probably limited [31]. Previous research has shown that during the course of their illness, COPD patients gradually decline with respect to pulmonary function and with respect to physical and other domains of QoL [37,50]. This process of deterioration can only be retarded, with medication for instance, but not stopped [36].…”
Section: Quality Of Lifementioning
confidence: 88%
“…5,6,[15][16][17][18] Recent studies suggest that exacerbation risk is related to previous exacerbation history, physical activity levels, presence of particular comorbidities such as gastro-oesophageal reflux, and disease severity. 19 Current therapies are known to decrease the frequency of these future exacerbation events.…”
Section: Exacerbations As An Example Of the Link Between Best Currentmentioning
confidence: 99%